Numerical simulation of coal breaking characteristics by continuous water jet based on ALE algorithm - Congmeng HAO; Xuexi CHEN; Qingquan LIU; Feiyang JIN (Meikuang Anquan, 2024)
In order to explore the influence of environmental media on the characteristics of water jet coal breaking, ALE algorithm and LS-Dyna software are used to carry out numerical simulation of continuous water jet impact coal breaking and the characteristics of water jet propagation, coal breaking characteristics and time-varying characteristics of the relationship between the two coal breaking depths under the submerged and non-submerged environments are analyzed. The results show that because of the large loss of water jet, the jet velocity in submerged environment is much lower than that in non-submerged state. Under the obstruction of environmental medium, the submerged jet diverges and increases the area of broken coal, resulting in the increase of the area of broken coal and the decrease of the depth, but the damage element does not change much. It is necessary to prolong the impact time reasonably or reduce the spacing of boreholes when coal caving is carried out in submerged environment.